PERATURAN DAN KEBIJAKAN NASIONAL DALAM PENGELOLAAN PERKEBUNAN KELAPA SAWIT DI INDONESIA: ASPEK BUDIDAYA, PEMANFAATAN, PENGEMBANGAN, PERIZINAN, TATA RUANG, DAN TANGGUNG JAWAB SOSIAL PERUSAHAAN TERHADAP MASYARAKAT LOKAL - Gunawan Widjaja (INTELIGENSIA MEDIA, 2025)
This study analyses national regulations and policies on oil palm plantation management in Indonesia, covering aspects of cultivation, utilisation, development, licensing, spatial planning, and corporate social responsibility towards local communities, using a legal-normative approach through a literature review of Law 39 of 2014 on Plantations, its derivative regulations, ISPO certification, and various related literature. The results of the analysis show that the national regulatory framework is normatively comprehensive in regulating the principles of sustainability, core-plasma partnerships, and CSR obligations. but its implementation in the field still faces gaps such as the lack of synchronisation between permits and spatial planning, recurring agrarian conflicts, formalistic implementation of CSR, and unequal benefits for smallholders. Therefore, regulatory harmonisation, strengthened supervision, digitisation of licensing, and empowerment of local mediation are needed to realise sustainable, inclusive, and socially equitable palm oil management.